Identification and Characterization of Parasite Neopharyngodon Sp. From Wall Lizard (Gecko) Of Nepal - Pun, Shyam K.; Maharjan, Mahendra (Journal of Institute of Science and Technology, 2016)
A total of 25 wall lizards (15 Hemidactylus brookii brookii and 10 H. platyurus) were examined for nematode parasite Neopharyngodon sp. from Kirtipur, Nepal. Neopharyngodon sp. were taxonomically identified and showed characteristics like small size (1.375-1.5mm x 0.225-0.25mm), mouth with two lips, oesophagus (0.35mm x 0.03mm), oesophagus bulb (0.092mm) and pointed tail with size one-third of the whole body length. Twenty percent of H. brookii brookii harbored the nematode parasite with average parasitic intensity of 4.3 while 80% of H. platyrus showed Neopharyngodon sp with parasitic intensity of 4. Journal of Institute of Science and Technology Vol. 21, No. 1, 2016, Page: 52-55